PEMERIKSAAN TEKANAN DARAH DAN KOMUNIKASI, INFORMASI, EDUKASI PENCEGAHAN DAN PENGENDALIAN PENYAKIT HIPERTENSI DI SRIMULYO DAN TIRTONIRMOLO- BANTUL - Agustin, Helfi; Sari, Retno Purnama; Syalsabilla, Merietha Agusti (LPPM IST AKPRIND Yogyakarta, 2022)
ABSTRACT Hypertension is a major public health problem in the world and in Indonesia. The prevalence of hypertension in Indonesia according to baseline health research of year 2018 is 34.1%. People need to implement a healthy lifestyle as an effort to prevent hypertension. Health information which repeated continuesly will encourage lifestyle changes in the community. The purpose of this community service activity was to increase knowledge about hypertension through a good understanding, especially about the definition, causes, signs and symptoms, prevention and treatment of hypertension. The service method was by providing counseling to 25 families of Srimulyo village-Piyungan subdistrict, and 40 families in Padokan Kidul, Kasihan subdistrict, Bantul Regency. Counseling was carried out directly by implementing health protocols and using leaflets and posters. The evaluation of this service activity uses a pretest and posttest design. Data analysis used paired t-test. The results of the t-test obtained p-value 0.000 <0.05 which indicates that there is a difference in the average knowledge of the audience about hypertension before and after counseling. This service activity is statistically proven to have increased public knowledge about hypertension prevention. Audience awareness is expected to be followed up with early detection of hypertension by checking blood pressure regularly and implementing a clean and healthy lifestyle.